دور امتحان تقييم المكتسبات في علاج تدني مستوى متعلمي اللغة العربية في السنة الخامسة من التعليم الابتدائي - الأسود ايمان; حرزولي تيسير (University of El-oued, 2025)
تنطلق هذه الدراسة الموسومة بــــ: "دور امتحان تقييم المكتسبات في علاج تدني مستوى متعلمي اللغة العربية في السنة الخامسة من التعليم الابتدائي"، من مقارنة بين امتحان نهاية مرحلة التعليم الابتدائي وامتحان تقييم المكتسبات، من خلال استقراء وتحليل وثائق كل منهما في الجانب النظري، وكذا الجانب التطبيقي الميداني؛ حيث تتبعنا تطور نتائج عينة من تلاميذ الصف الخامس من التعليم الابتدائي خلال الفصول الثلاثة لمعرفة مدى نجاعة هذا التقييم في كشف نقاط الضعف وعلاجها من خلال التقييم الدوري والمستمر من بداية السنة الدراسية إلى نهايتها. إضافة إلى ذلك قدمنا استبانة لمعلمي السنة الخامس من التعليم الابتدائي لمعرفة مدى فاعلية هذا التقييم من وجهة نظرهم، ومدى تكيفهم معه. ومن هنا توصلنا إلى أن امتحان تقييم المكتسبات يمثل خطوة مهمة نحو تطوير المنظومة التربوية في الجزائر، خاصة في تعليم اللغة العربية التي تعد من أهم الكفاءات ذات الطابع التواصلي. أثبتت النتائج التي توصلنا إليها إلى أن تقييم المكتسبات يساعد في تشخيص نقاط الضعف لدى التلاميذ على مستوى كل كفاءة، مما يسمح للمعلم اتخاذ إجراءات علاجية من خلال تعديل استراتيجياتهم التربوية، وهذا لا يتحقق إلا إذا بتظافر جهود كل الجهات الوصية، مع تدارك كل النقائص التي ما زالت تحيط بهذا التقييم. This study, entitled "The Role of the Achievement Assessment Examination in Addressing the Low Level of Arabic Language Learners in the Fifth Year of Primary Education", is based on a comparison between the end-of-primary education exam and the Achievement Assessment Examination, using extrapolation and analysis of both exams—practically and theoretically. We followed the progress of a sample of fifth-grade primary students over three semesters to evaluate the effectiveness of this assessment in identifying and addressing weaknesses, through periodic and continuous evaluation from the beginning to the end of the school year. Additionally, we conducted a questionnaire with fifth-grade Arabic language teachers to assess the effectiveness of this exam from their point of view and their level of adaptation to it. Our findings show that the Achievement Assessment Examination is a valuable tool for developing the educational system in Algeria, especially in the teaching of Arabic, which is one of the most important communicative competencies. Our results demonstrate that acquisition assessment helps in diagnosing students’ weaknesses at the level of each competency. It enables teachers to take remedial action by adapting their educational strategies. This can only be achieved through the concerted efforts of all relevant stakeholders, while also addressing the existing shortcomings of the assessment system.
مذكرة .ماستر . لسانيات عامة. 2025
Keywords: امتحان _ تقويم _ تقييم _ الاكتساب _ تقييم المكتسبات _ كفاءة.; exam – evaluation – assessment – acquisition – assessment of acquisitions – competency